Childhood ADHD and Growth in Adolescent Alcohol Use: The Roles of Functional Impairments, ADHD Symptom Persistence, and Parental Knowledge - Molina, Brooke S. G. (2012)
Research on the relation between childhood Attention-Deficit/Hyperactivity Disorder (ADHD) and adolescent alcohol use has found mixed results. Studies are needed that operationalize alcohol use in developmentally appropriate ways and that test theoretically plausible moderators and mediators in a longitudinal framework. The current study tested childhood ADHD as a predictor of alcohol use frequency at age 17, and age-related increases in alcohol use frequency, through adolescence for 163 adolescents with ADHD diagnosed in childhood and 120 adolescents without ADHD histories. Childhood ADHD did not predict either alcohol outcome. However, parental knowledge of the teen’s friendships, activities, and whereabouts moderated the association such that childhood ADHD predicted alcohol use frequency at age 17 when parental knowledge was below median levels for the sample. Mediational pathways that explained this risk included social impairment, persistence of ADHD symptoms, grade point average, and delinquency. Social impairment was positively associated with alcohol use frequency through delinquency; it was negatively associated with alcohol use frequency as a direct effect independent of delinquency. These nuanced moderated-mediation findings help to explain previously inconsistent results for the ADHD-adolescent alcohol use association. The findings also imply that future research and intervention efforts should focus on ADHD-related social and academic impairments as well as symptom persistence and parenting efforts.